Extensively Drug-Resistant Pseudomonas aeruginosa Isolates Containing blaVIM-2 and Elements of Salmonella Genomic Island 2: a New Genetic Resistance Determinant in Northeast Ohio - Perez, Federico (2014)
Carbapenems are a mainstay of treatment for infections caused by Pseudomonas aeruginosa. Carbapenem resistance mediated by metallo-β-lactamases (MBLs) remains uncommon in the United States, despite the worldwide emergence of this group of enzymes. Between March 2012 and May 2013, we detected MBL-producing P. aeruginosa in a university-affiliated health care system in northeast Ohio. We examined the clinical characteristics and outcomes of patients, defined the resistance determinants and structure of the genetic element harboring the blaMBL gene through genome sequencing, and typed MBL-producing P. aeruginosa isolates using pulsed-field gel electrophoresis (PFGE), repetitive sequence-based PCR (rep-PCR), and multilocus sequence typing (MLST). Seven patients were affected that were hospitalized at three community hospitals, a long-term-care facility, and a tertiary care center; one of the patients died as a result of infection. Isolates belonged to sequence type 233 (ST233) and were extensively drug resistant (XDR), including resistance to all fluoroquinolones, aminoglycosides, and β-lactams; two isolates were nonsusceptible to colistin. The blaMBL gene was identified as blaVIM-2 contained within a class 1 integron (In559), similar to the cassette array previously detected in isolates from Norway, Russia, Taiwan, and Chicago, IL. Genomic sequencing and assembly revealed that In559 was part of a novel 35-kb region that also included a Tn501-like transposon and Salmonella genomic island 2 (SGI2)-homologous sequences. This analysis of XDR strains producing VIM-2 from northeast Ohio revealed a novel recombination event between Salmonella and P. aeruginosa, heralding a new antibiotic resistance threat in this region's health care system